2018
DOI: 10.18517/ijaseit.8.5.3804
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Papaya Seeds as Natural Coagulant for Synthetic Textile Coloring Agent Wastewater Treatment

Abstract: Textile wastewater contains many pollutants which is hazardous if directly discharged. Various technologies such as adsorption, advanced oxidation processes, biological treatment, membrane technology, coagulation, and flocculation have been explored and utilized to treat textile wastewater. However, coagulation followed by flocculation is still widely used. Usually, inorganic salts such as alum, ferric chloride, PAC, are widely used to treat textile wastewater. However, utilization of inorganic salts poses som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 34 publications
2
10
0
Order By: Relevance
“…The removal percentages for COD and TSS were up to 48.22 and 81.58%, respectively. Kristianto et al (2018) studied the use of papaya seed powder to remove color in synthetic textile wastewater. The result shows the percentage of removal of 84.77% with optimum conditions were found in coagulant dosage is 0.57 g L À1 , and pH 1.97.…”
Section: Trigonella Foenum-graecum and Okramentioning
confidence: 99%
“…The removal percentages for COD and TSS were up to 48.22 and 81.58%, respectively. Kristianto et al (2018) studied the use of papaya seed powder to remove color in synthetic textile wastewater. The result shows the percentage of removal of 84.77% with optimum conditions were found in coagulant dosage is 0.57 g L À1 , and pH 1.97.…”
Section: Trigonella Foenum-graecum and Okramentioning
confidence: 99%
“…The authors reported 90-99% removal of water bacteria after using this natural coagulant in addition to its coagulation role. Carica papaya seeds are another natural coagulant obtained from tropical trees and characterized by cystine protease proteins (water-soluble and positively charged proteins), which are also utilized as a putative natural coagulant [123]. In a study done by Unnisa et al [124], Carica papaya seeds were used as a pre-treatment for SODIS to reduce water turbidity and inactivate coliform bacteria.…”
Section: Coagulant Pre-treatment To Solar Disinfectionmentioning
confidence: 99%
“…Alum based sludge for example was described to be difficult to dewater (Gupta et al, 2011). Another potential problem is associated with health issues such as Alzheimer's, and dementia (Kristianto, Kurniawan, & Soetedjo, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They successfully reached 67.66%, 96.86% and 91.12% COD, turbidity and colour removal, respectively. Many researchers investigated the performance of other natural coagulants such as potato starch (Ahmad, 2018), papaya seeds (Kristianto et al, 2018), sago, chitin (Saritha, Karnena, & Dwarapureddi, 2019) and okra (Freitas et al, 2015) as possible alternatives to the chemical coagulants. Strychnospotatorum (Nirmali seeds) and Eirchorrniacrassipes (water hyacinth) were seen to give better reduction for total suspended solids (TSS), COD and biological oxygen demand (BOD) over alum (Prabhakaran, Manikandan, & Boopathi, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation